Landmark Identıfıcatıon Errors And Reasons In Cephalometrıc Analysıs - Türker Sandallı; Uğur Bilgiç (Galenos Yayinevi, 1988)
Landmark identification errors in latero-skull x-rays of 15 dental students was determined to measure by three resarchers on two occasions. Errors were found to be high on landmarks as I apex, Ī apex, Go, A, Po, B, Or and D. Thoughts on this subject were discussed